2019
DOI: 10.1097/sla.0000000000002707
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Robotic Approach and ERAS Pathway Optimizes Outcomes and Cost for Pancreatoduodenectomy

Abstract: ERAS implementation is independently associated with cost savings for pancreatoduodenectomy. A combination of ERAS and robotic approach synergistically decreases hospital stay and overall cost compared with other strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 56 publications
2
52
0
Order By: Relevance
“…This network analysis showed statistically significant longer operative time for LapPD and RobPD, might be due to the learning curve and docking of the robot. Few articles reported the analysis of costs with a trend towards greater cost in minimally invasive techniques, mainly RobPD, probably due to the maintenance of instrument and equipment costs [77]. However, the reduced postoperative complications, hospital length of stay, and hospital readmissions may suggest a presumed ultimate cost-effectiveness [78].…”
Section: Discussionmentioning
confidence: 99%
“…This network analysis showed statistically significant longer operative time for LapPD and RobPD, might be due to the learning curve and docking of the robot. Few articles reported the analysis of costs with a trend towards greater cost in minimally invasive techniques, mainly RobPD, probably due to the maintenance of instrument and equipment costs [77]. However, the reduced postoperative complications, hospital length of stay, and hospital readmissions may suggest a presumed ultimate cost-effectiveness [78].…”
Section: Discussionmentioning
confidence: 99%
“…The medicoeconomic impact of ERAS for rectal surgery is difficult to demonstrate. However, recent publications have underlined the cost benefit of enhanced recovery after hepatectomy or pancreatectomy. For colorectal surgery, a systematic review underlined the poor quality data currently available, but showed that ERAS was less costly and more effective than proctectomy alone.…”
Section: Discussionmentioning
confidence: 99%
“…The length of hospital stay is controversial and reported to be significantly shorter in RPD than in OPD and even laparoscopic PD (LPD), whereas other studies reported equal times between RPD and OPD [16,20,31,58,59,62,63].…”
Section: Robotic Pancreatoduodenectomymentioning
confidence: 99%